Graduate Employability and Entrepreneurship in Records Management: Unexplored Potential Business in Commercial Records Center - Yatin, Saiful Farik Mat; Masron, Mohd Zairul; Hussin, Nurussobah; Shuhaimi, Hasnah; Kadir, Mohd Razilan Ab; Wah, Yap Bee (Journal of Informatics and Mathematical Sciences, 2017)
This paper aimed to determine if records management students/graduates (RMS) in records management program (RMP) and their academic-acquired skills and competencies are related to their field of study and their present occupations. Three (3) years of Graduate Tracer Study instrument was analyzed to gather the quantitative data focusing on the students of Records Management Program (RMP) in UniversitiTeknologi MARA (UiTM), Malaysia. The results further proved that RMP produces marketable and appropriately trained graduates but the majority landing NOT in course-related jobs within a short period of time after graduation. RMS is still low in initiating their own business like what been offered by Commercial Records Center (CRC). RMS should consider initiating a business offered by CRC. Therefore, in-depth understanding of the benefits of the CRC and their services is needed to ensure the potential of CRC business and services for RMS to consider initiating their own business in future.